Persistence of Imported Malaria Into the United Kingdom: An Epidemiological Review of Risk Factors and At-risk Groups. (7th December 2018) - Moyo, Qubekani M; Besser, Martin; Lynn, Roderick; Lever, Andrew M L
Abstract: Background: The United Kingdom documented a decline of >30% in imported cases of malaria annually between 1996 and 2003; however, there are still approximately 1700 cases and 5–10 deaths each year. Prophylaxis health messages focus on families returning to their country of origin. Methods: We reviewed 225 records of patients seen in Cambridge University Hospital Foundation Trust [CUHFT], a tertiary referral center in Cambridge, England. All records of patients seen in CUHFT between 2002–2016 were analyzed in the context of national figures from Public Health England. Results: Between 2004–2016, there was no decrease in imported cases of malaria locally or nationally. Plasmodium falciparum remains responsible for most imported infections (66.7%); Plasmodium vivax contributed 15.1%, Plasmodium malariae 4%, and Plasmodium ovale 6.7%; 7.5% (17/225) of patients had an incomplete record. Most cases were reported in people coming from West Africa. Sierra Leone and the Ivory Coast had the highest proportions of travelers being infected at 8 and 7 per 1000, respectively. Visiting family in the country of origin (27.8%) was the commonest reason for travel. However, this was exceeded by the combined numbers traveling for business and holidays (22.5% and 20.1%, respectively). Sixty percent of patients took no prophylaxis. Of those who did, none of the patients finished their chemoprophylaxis regimen. Conclusions: Significant numbers of travelers to malarious countries still take no chemoprophylaxis. Health advice about prophylaxis before travel should be targeted not only at those visiting family in their country of origin but also to those traveling for holiday and work. Abstract : After a decline in the early 2000s, imported malaria has reached a plateau. Focus on people returning to countries of origin as the at-risk population oversimplifies intervention planning. Holiday and business reasons together exceed this as a risk factor.